Patella-patellar tendon angle in relation to the medial patellar plica syndrome, chondromalacia patella, and infrapatellar fat pad syndrome. - Taeho Kim; Jin Kyem Kim; Hong Seon Lee; Dong Kyu Kim (PLoS ONE, 2022)
The patella-patellar tendon angle (PPTA) assessing the sagittal patellar tilt was reported to be related with anterior knee pain. Herein, clinical effect of PPTA in patients with medial patellar plica (MPP) syndrome, chondromalacia patella, and infrapatellar fat pad (IPFP) syndrome, the most common causes of anterior knee pain, was evaluated. In this retrospective study, 156 patients with anterior knee pain who underwent magnetic resonance imaging (MRI) and arthroscopic surgery that confirmed isolated MPP syndrome, chondromalacia patella, or IPFP syndrome from June 2011 to January 2021 were included in the study group and 118 patients without knee pathology on MRI during the same period were included in the control group. The PPTA was measured on knee MRI and compared between the two groups. A receiver operating characteristic (ROC) analysis was used to evaluate the value of PPTA for predicting the risk of patellofemoral joint disorder. The mean PPTA was significantly smaller in study group (138.1 ± 4.2°) than control group (142.1 ± 4.3°) (p < 0.001). However, there was no significant difference in PPTA among the patients with MPP syndrome, chondromalacia patella, and IPFP syndrome. Furthermore, the ROC analysis revealed that the area under curve, sensitivity, and specificity for predicting the risk of patellofemoral joint disorders were 0.696, 70.3% and 57.6%, respectively, at a PPTA cutoff of 138.3°. Therefore, the smaller PPTA may be associated with MPP syndrome, chondromalacia patella, and IPFP syndrome. Furthermore, PPTA could be a predictive factor for the risk of patellofemoral joint disease in patients with anterior knee pain.